Analysis Stylistic in The Novel Sepi by Pijar Psikologi: Analisis Stilistika dalam Novel Sepi Karya Pijar Psikologi - Annisa Amelia Zakiyah; Ahada Wahyusari; Dody Irawan (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This research describes stylistics as the science that delves into literary studies by applying the principles of stylistic language found in the novel "Sepi" by Pijar Psikologi. The object of this research is the novel "Sepi" by Pijar Psikologi. The research method used in this study is descriptive qualitative. The research instrument used in this study is the researcher herself. The data collection techniques used are reading and note-taking techniques. The data obtained from the novel "Sepi" by Pijar Psikologi are types of language styles such as comparison, linkage, contradiction, and satire. These are divided into several language styles: personification, metonymy, hyperbole, pleonasm, metaphor, association, allegory, allusion, antithesis, litotes, euphemism, synesthesia, eponym, irony, and cynicism. The diction or word choices found in the research data from the novel "Sepi" by Pijar Psikologi. The types of diction found in the research results are connotation, denotation, conceptual, specific, and general terms.